Penerapan Silvo-apifisheries dalam pengembangan Ekowisata Pendidikan di Sekitar Hutan Lindung Gunung Ambawang-Pemancing (HL-GAP) Kubu Raya - Normagiat, Sigit; Wulan Sari, Dahlia; Muhammad Syaifudin, Syarif (Jurnal Ilmiah Pangabdhi, 2024)
The priority problem that needs to be overcome in Sungai Deras Village by the PKM team is to restore vegetation lost by land clearing activities in order to maintain the protection function of the area. The availability of nectar from flowering vegetation as a source of feed for kelulut bees cultivated by residents is still limited, the availability of sufficient feed will affect the volume and quality of honey produced. The knowledge of community members related to the technology and management of kelulut honey cultivation is still relatively low. In addition, the tourist area in Sungai Deras village needs the addition of better attractions and promotions so that it is increasingly known and in demand by the wider community in West Kalimantan and at the national level. The purpose of this community empowerment activity is expected that honey bee cultivation can also be of tourist attraction value by making the land around existing tourist sites into kelulut cultivation land. This business is not only economic, ecologically also has educational value because it can be used as a location for practice and research for students, lecturers and the general public who want to learn about forest ecosystems and kelulut bee cultivation while traveling (Ecoedutourism). The solution offered by the PKM team is to organize and plant to enrich the number and type of vegetation feed for kelulut bees using an integrated cultivation pattern between forestry, bees and fisheries in one location (SIlvoapifisheries) which also has ecotourism and educational values. PKM activities consist of technical guidance on kelulut cultivation, installing 20 kelulut colonies in stup which will be further developed communally, revegetating the land around kelulut cultivation with types of fruit, flower and medicinal plants. It is hoped that the enrichment of vegetation and cultivating kelulut can maintain the function of protection control and increase community income from the tourism sector.